Glass Fiber-Reinforced Sprayed Concrete: Physical, Mechanical, and Durability Properties - Kabay, Nihat; Amed, Bahadur (ASCE-AMER SOC CIVIL ENGINEERS, 2021)
The physical, mechanical, and durability properties of glass fiber-reinforced concrete (GFRC) incorporating fly ash, slag, and acrylic polymer with different fiber contents were studied. The use of pozzolanic materials and polymer modified the fresh and physical properties by improving the workability and reducing the water absorption and density of the GFRC mixes. The flexural strength of mixes incorporating fly ash and slag improved with increasing fiber content. The inclusion of acrylic polymer improved the deformation capability of all mixes. Analysis of the fracture surface of the GFRC samples showed the dependence of toughness with the amount of fiber pullout. Wet-dry cycles and exposure to high temperature resulted in significant reductions in mechanical properties in terms of flexural strength and toughness. The normalized toughness values of mixes exposed to 800 degrees C and wet-dry cycles are found to be correlated with each other. Therefore, exposure to high temperature might provide rapid results in predicting long-term GFRC degradation and might be an alternative to wet-dry cycles.
Keywords: Glass fiber– reinforced concrete; Fly ash; Slag; Polymer; Durability; Mechanical properties; Physical properties; FLY-ASH; CEMENT; GRC; PREDICT; Construction & Building Technology; Engineering; Materials Science